Teaching EFL in Rural Areas: Addressing Challenges and Identifying Effective Strategies - Tasya Herdiyanti; Annisa Meliani Putri; Qhintara Afni Farhana; Eliwarti (Universitas Islam Negeri Palopo, 2025)
This study employs a Systematic Literature Review (SLR) to investigate the challenges and strategies of teaching English as a Foreign Language (EFL) in rural areas. A total of 14 empirical studies published between 2015 and 2024 were analyzed from databases including ERIC, Publish or Perish, and Google Scholar. Findings indicate that the most frequently reported challenge was the lack of teaching resources and facilities (71%), followed by limited teacher training opportunities (57%), teachers’ non-English educational background (43%), and cultural adaptation difficulties (36%). Strategies to address these issues included the use of culturally relevant materials (64%), community and parental engagement (50%), direct and simplified teacher talk (43%), and the integration of technology where possible (36%). These results highlight the urgent need for targeted professional development, improved infrastructure, and policy support to ensure equitable access to quality English education in rural settings.